COACHING CLINIC UNTUK PEMAIN PICKLEBALL DI JAKARTA INDONESIA - susilo; Boyke (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract The most important component in sports coaching is the coach. A common problem with pickleball is the lack of professional coaches who understand the sport. Considering that pickleball is a sport that is just developing in Indonesia, it is necessary for the attention and intervention of stakeholders to help create competent pickleball coaches to produce outstanding athletes in the future. This is because the function and role of a coach is closely related to the achievements of athletes. Many pickleball coaches do not have a competency certification in the field of pickleball coaching. So that the competence of trainers is something that needs to be developed gradually starting from the regional, national and international levels. The main target of this international collaborative community service activity is pickleball players in Indonesia. Service activities are carried out by providing knowledge both theoretical and practical about coaching in pickleball. Through this first phase of service activities, 38 trainers have a pickleball competency certification at the regional level. Community service activities at the coaching clinic for pickleball players in Jakarta Indonesia received an enthusiastic response from the activity participants. This can be seen from the coach's satisfaction with the pickleball clinic coaching activity which is very high at 88.86%. Abstrak Komponen paling penting dalam pembinaan olahraga yakni pelatih. Permasalahan umum yang terjadi di olahraga pickleball adalah minimnya pelatih yang professional dan mengerti keilmuan olahraga. Mengingat cabang olahraga pickleball adalah olahraga yang baru berkembang di Indonesia, untuk itu diperlukan kepedulian dan campur tangan para steakholder dalam membantu menciptakan pelatih pickleball yang berkompeten agar tercipta atlet-atlet yang berprestasi dimasa mendatang. Sebab, fungsi dan peran seorang pelatih sangat erat hubungannya dengan capaian prestasi yang diukir oleh atlet. Banyak pelatih pickleball yang tidak memiliki sertifikasi kompetensi di bidang kepelatihan pickleball. Sehingga kompetensi pelatih merupakan suatu hal yang perlu untuk terus dikembangkan secara berjenjang dimulai dari tingkat daerah, nasional dan internasional. Sasaran utama kegiatan pengabdian kepada masyarakat kolaboratif internasional adalah pemain pickleball di Indonesia. Kegiatan pengabdian dilakukan dengan pemberian pengetahuan baik teori maupun praktek tentang kepelatihan di pickleball. Melalui kegiatan pengabdian tahap pertama ini menghasilkan 38 pelatih yang memiliki sertifikasi kompetensi pelatih pickleball tingkat daerah. Kegiatan pengabdian kepada masyarakat coaching clinic untuk pemain pickleball di Jakarta Indonesia mendapatkan respon yang antusias dari para peserta kegiatan. Hal ini terbukti dari kepuasaan pelatih terhadap kegiatan coaching clinic pickleball sangat tinggi yaitu sebesar 88,86%.